From drugs to biomaterials: a review of emerging therapeutic strategies for intervertebral disc inflammation - Yang, Shuhan; Jing, Shaoze; Wang, Shanxi; Jia, Fajing (Frontiers in Cellular and Infection Microbiology, 2024)
Chronic low back pain (LBP) is an increasingly prevalent issue, especially among aging populations. A major underlying cause of LBP is intervertebral disc degeneration (IDD), often triggered by intervertebral disc (IVD) inflammation. Inflammation of the IVD is divided into Septic and Aseptic inflammation. Conservative therapy and surgical treatment often fail to address the root cause of IDD. Recent advances in the treatment of IVD infection and inflammation range from antibiotics and small-molecule drugs to cellular therapies, biological agents, and innovative biomaterials. This review sheds light on the complex mechanisms of IVD inflammation and physiological and biochemical processes of IDD. Furthermore, it provides an overview of recent research developments in this area, intending to identify novel therapeutic targets and guide future clinical strategies for effectively treating IVD-related conditions.